Security Attacks in Wireless Sensor Networks - Bhagavathi Gurajada, Lalitha; Deepthi Rajaputra, Sai; Gogineni, Indira; Shaik, Riaz (International Journal of Engineering and Technology, 2018)
In todayâ€™s world, Security is the prime concern for each application. Network security and Computer protection are the serious issues. A broad range of Wireless Sensor Networks (WSNs) applications[1][15] are widely used in military, researches etc. The key subject of computing is to provide network security several types of attacks are increasing day by day. The attacks present in different layers are produced due to the susceptibilities present in the layers. The Seven layers in OSI model are formulated to convey the information from highest layer to lowest layer. Broadcast of data gets modified according to the layer in which it lies. Individually every layer is weak to different types of attacks. This paper models about the different attacks present in each layer of OSI.Â Â